2013
DOI: 10.1021/jf401102a
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Controlled-Release Fertilizer with Water Retention via Atom Transfer Radical Polymerization of Acrylic Acid on Mussel-Inspired Initiator

Abstract: This work reports a polydopamine-graft-poly(acrylic acid) (Pdop-g-PAA)-coated controlled-release multi-element compound fertilizer with water-retention function by a combination of mussel-inspired chemistry and surface-initiated atom transfer radical polymerization (SI-ATRP) techniques for the first time. The morphology and composition of the products were characterized by transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), gel permeation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…It is expected that these synthesized graft copolymers have great potential in biomedical, such as tissue engineering scaffolds with double-responsive and antifouling properties. Linear form of PAA has been one of the most extensively studied industrially important watersoluble polymer [16]. It has significant pH response, which is mainly due to high concentrations of -COOH groups [17,18], and therefore it is widely used as pH-sensitive drug delivery systems [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that these synthesized graft copolymers have great potential in biomedical, such as tissue engineering scaffolds with double-responsive and antifouling properties. Linear form of PAA has been one of the most extensively studied industrially important watersoluble polymer [16]. It has significant pH response, which is mainly due to high concentrations of -COOH groups [17,18], and therefore it is widely used as pH-sensitive drug delivery systems [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Among these slow-release fertilizers (SRF), the major categories are fertilizers coated with different materials. Recently, a number of materials have been tested: biodegradable polymers (Wu and Liu, 2008;Ao et al, 2013;Jia et al, 2013;Lubkowski et al, 2015), superabsorbent polymers (Liang et al, 2007;Teodorescu et al, 2009), commercial polymers (Figueiredo et al, 2012;Silva et al, 2012;Ma et al, 2013), oxides (Zhang et al, 2014) and fly ash (Dong et al, 2016). More specifically for MAP, a previous study has shown that when P is more slowly released from a thin polymer coated-MAP fertilizer granule, it increased P availability, P uptake and P use efficiency by barley plants (Pauly et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The release rates for both samples were always higher in basic solution than in acidic or neutral solutions. These results were attributed to the deprotonation of the carboxylic groups in the basic solution, and the strong electrostatic repulsion between the carboxylic groups also make the network expand, which is convenient for the nutrients to pass through the network . In contrast, the protonation of carboxylic groups at a low pH level prevented the efficient anion–anion electrostatic repulsion, and subsequently causes a shrinkage of the network, which is unfavorable for the transportation of nutrients .…”
Section: Resultsmentioning
confidence: 99%